Dampak CAR, LDR, NPL, dan BOPO Terhadap ROA Pada Bank Komersial yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2023 - P.E, Yosephien Angelina Yulia; Rudianto, Louis Yonathan (Excellent, 2025)
The purpose of this study was to see the impact of CAR, LDR, NPL, BOPO on ROA. The sample in this study was 10 banks. Data were analyzed using descriptive statistical tests, classical assumption tests, multiple linear regression analysis, t-tests and coefficients of determination. Based on the results of the classical assumption test, the CAR, LDR, NPL, BOPO variables are not multicollinear, not autocorrelated, not heteroscedastic and the data is normal. The results of the study showed that the impact of CAR on ROA was negative and not significant, the impact of LDR on ROA was negative and significant, the impact of NPL was negative and significant on ROA. The impact of BOPO was positive and significant on ROA. The impact of the independent variable on the dependent variable was 70.4%, the remaining 29.6%.